Frequency detection for rotor telemetry system - Wang, Zhisheng (2018)
A microcontroller is a single integrated circuit dedicated to perform a specific operation in an embedded system. Often known as embedded controller or Microcontroller Unit (MCU), it is used in multiple industries and applications, ranging from facilitating the simplest operation of electromechanical systems found in our daily convenience items, such as televisions, printers, mobile phones and Automated Teller Machines (ATMs), to more sophisticated and critical functions in aircrafts, vehicles, medical and life-support systems and even to the extent of regulating the operations of an artificial organ. A Microcontroller Unit has one or more processor cores along with memory and programmable input/output peripherals. Such peripheral functions include Analog-to-Digital Converters (ADC), Real-Time Clock (RTC), Liquid Crystal Display (LCD) controllers and Universal Serial Bus (USB) connectivity. Signal processing is extremely essential especially in the fault detections of Rotor Telemetry systems. Signals and current readings from the sensors in the RTS are processed and transformed into the frequency domain for fault detection/analysis. Therefore, this project presents how Teensy 3.2, a complete USB-based microcontroller development system will be used to perform Analog-to-Digital Conversion (ADC) via the implementation of Fast Fourier Transform (FFT) algorithm on Arduino IDE to detect the frequency components of Multi-Tone and Single-Tone signals. Comparisons have also been done to find out how certain factors, such as sample size and sampling frequency of the FFT, may affect the results of the FFT.